THE INFLUENCE OF TAHAPAN BCA'S QUALITY TO CUSTOMER SAVING DECISION THROUGH BRAND IMAGE OF BANK CENTRAL ASIA - Harvellino Fernando; Meylani Tuti (Human Capital Development, 2022)
The purpose of this study was to analyze and determine the effect of the quality of tahapan bca on saving decision through brand image of Bank Central Asia. The population in this study are consumers who have made savings and transactions more than twice and the sampling technique used is accidental sampling with a total of 254 respondents. The data analysis method used is the Structural Equation Model using Smart-PLS 3. The results showed that the quality of tahapan bca had a significant effect on saving decisions. On the other hand, the quality of tahapan bca has an influence on brand image. Meanwhile, brand image has a significant effect on saving decisions.